Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
P=\(\frac{2\sqrt{x}}{\sqrt{x}+m}+\frac{2\sqrt{x}}{\sqrt{x}-m}-\)\(\frac{m^2}{4x-4m^2}\)
= \(\frac{8\sqrt{x}\left(\sqrt{x}-m\right)+8\sqrt{x}\left(\sqrt{x}+m\right)-m^2}{4x-4m^2}\)
=\(\frac{8\sqrt{x}\left(\sqrt{x}-m+\sqrt{x}+m\right)-m^2}{4x-4m^2}\)
=\(\frac{8\sqrt{x}.2\sqrt{x}-m^2}{4x-4m^2}\)
=\(\frac{16x-m^2}{4x-4m^2}\)
\(A=1+\frac{3}{m-1}\cdot\sqrt{m^2-4m+4}\)
\(=1+\frac{3}{m-1}\cdot\sqrt{\left(x-2\right)^2}\)
\(=1+\frac{3}{m-1}\cdot\left|x-2\right|\)
\(=\frac{m-1}{m-1}+\frac{3\left(m-2\right)}{m-1}\)
\(=\frac{4m-7}{m-1}\)
\(B=\sqrt{1-10x+25x^2}-4x\)
\(=\sqrt{\left(5x-1\right)^2}-4x\)
\(=\left|5x-1\right|-4x\)
\(a,\sqrt{\sqrt{17+12\sqrt{2}}}\)
\(=\sqrt{\sqrt{8+12\sqrt{2}+9}}\)
\(=\sqrt{\sqrt{\left[2\sqrt{2}+3\right]^2}}\)
\(=\sqrt{2\sqrt{2}+3}\)
\(=\sqrt{1+2\sqrt{2}+2}\)
\(=\sqrt{\left[1+\sqrt{2}\right]^2}\)
\(=1+\sqrt{2}\)
\(b,\sqrt{4+2\sqrt{3}}-\sqrt{21-12\sqrt{3}}\)
\(=\sqrt{3+2\sqrt{3}+1}-\sqrt{12-12\sqrt{3}+9}\)
\(=\sqrt{\left[1+\sqrt{3}\right]^2}-\sqrt{\left[2\sqrt{3}-3\right]^2}\)
\(=\left(1+\sqrt{3}\right)-\left(2\sqrt{3}-3\right)\)
\(=1+\sqrt{3}-2\sqrt{3}+3\)
\(=4-\sqrt{3}\)
chúc bn học tốt
\(A=\sqrt{\frac{5+\sqrt{21}}{5-\sqrt{21}}}+\sqrt{\frac{5-\sqrt{21}}{5+\sqrt{21}}}\)
\(=\sqrt{\frac{\left(5+\sqrt{21}\right)^2}{\left(5-\sqrt{21}\right)\left(5+\sqrt{21}\right)}}+\sqrt{\frac{\left(5-\sqrt{21}\right)^2}{\left(5-\sqrt{21}\right)\left(5+\sqrt{21}\right)}}\)
\(=\sqrt{\frac{\left(5+\sqrt{21}\right)^2}{4}}+\sqrt{\frac{\left(5-\sqrt{21}\right)^2}{4}}\)
\(=\frac{5+\sqrt{21}}{2}+\frac{5-\sqrt{21}}{2}=5\)
\(B=\sqrt{7+\sqrt{33}}+\sqrt{7-\sqrt{33}}\)
\(\Rightarrow\)\(\sqrt{2}B=\sqrt{14+2\sqrt{33}}+\sqrt{14-2\sqrt{33}}\)
\(=\sqrt{\left(\sqrt{11}+\sqrt{3}\right)^2}+\sqrt{\left(\sqrt{11}-\sqrt{3}\right)^2}\)
\(=\sqrt{11}+\sqrt{3}+\sqrt{11}-\sqrt{3}=2\sqrt{11}\)
\(\Rightarrow\)\(B=\sqrt{22}\)
a) \(\sqrt{11-2\sqrt{10}}\)
\(=\sqrt{10-2\sqrt{10}+1}\)
\(=\sqrt{\left(\sqrt{10}-1\right)^2}\)
\(=\sqrt{10}-1\)
b) \(\sqrt{21-6\sqrt{6}}\)
\(=\sqrt{\left(3\sqrt{2}\right)^2-2\cdot3\sqrt{2}\cdot\sqrt{3}+3}\)
\(=\sqrt{\left(3\sqrt{2}-\sqrt{3}\right)^2}\)
\(=3\sqrt{2}-\sqrt{3}\)
\(\sqrt{\left(2\sqrt{3}\right)^2-2.2\sqrt{3}.3+9}-2\sqrt{3}\)
\(\sqrt{\left(2\sqrt{3}-3\right)^2}-2\sqrt{3}\)
\(2\sqrt{3}-3-2\sqrt{3}\)
= -3